113 An interventional study to assess the incidence of vitamin b12/d3 deficiency among corporate employees. (24th April 2018) - Kapadia, Amar; Paliwal, Aditya; Rajesh, R
Abstract : Introduction: In spite of living in tropical climates, vitamin D3 deficiency is evident in urban. Indian population as a corporate lifestyle disorder; Office executives especially, are not exposed to sunlight due to changing lifestyles and long working hours. Incidence of vitamin B12 deficiency is observed to be high, due to predominantly vegetarian diets and insufficient consumption of dairy products, etc. Methods: This study was conducted at Occupational Health Centre, Hazira from September 2016 to January 2017. In the first phase, 300 executives were surveyed and subjected to analysis of blood levels of vitamin D3 and Vitamin B12.History of exposure to sunlight, exercise, dietary habits, medication etc. was obtained through a Screening Questionnaire before blood collection. In second phase, treatment was advised for three months including counselling for dietary modifications, increased sun exposure, etc. At the end of three months, repeat testing of Vitamins was done to assess the effectiveness. Results: 17.67% had vitamin B12 deficiency, 17.33% had vitamin D3 deficiency. Deficient vitamin B12 values were found in 53 subjects of which 61.5% were vegetarians, 39.5% nonvegetarians and 30.18% were having alcohol consumption. Deficient vitaminD3 values were found in 52 subjects of which 92% do not spend at least 10 min a day in sun without sunscreen. In second phase 51.62% had normal Vitamin D3 levels as compared to 8.33% in first phase and 92.95% had vitamin B12 levels normal in second phase as compared to 77.1% in first phase. Conclusion: Effectiveness of oral supplementation of B12/D3 is demonstrated by the results of the second phase of the survey. Increase in sun exposure, dietary modification and other lifestyle modifications were also effective. Office executives need to exercise outdoors and thus increase their exposure to sunlight to facilitate vitamin D absorption. Vitamin B12/D3 tests to be made a part of annual medical check up.